(untitled) (Tempo e Argumento, 2017)
This article aims to approach the relations between the internet, representation of the past, and public history. To do this, it resorts to analyzing the website and the Facebook page “As Mina na História” [“Chicks in History”], created in June 2015. In this examination, it explores issues such as the type of representation of the past provided in this virtual space, the profile of its audience, and the language used. In order to move forward in these issues, brief comments are made about the teaching of women’s history in Brazil. Finally, we seek, through this approach, to propose some reflections about the public history that has been practiced in the country, beyond the issue of enlargement of the audience ‘consuming’ history. Keywords: Representation; Public History; Internet; Women.